Security Lock System for Fake Traits Based on Image Processing (International Journal of Engineering and Computer Science, 2015)
As the number of security issuesincreased from day to day,we have to improve thesecurity in efficient way.In the biometric signalbased security system the major problems is toensure the actual presence of real trait in contrasttoa fake ,self-manufactured,synthetic,reconstructedtraits.In this paper we propose a security locksystem which provide security with combination offingerprint,iris and palm images as biometricinput.And we also include the authenticationsystem for fake traits like silicon,playdoh,gelatinimages by adding liveness assessment in a fast,userfriendlyand non-intrusive manner through theimage quality assessment method.In this paper weinclude 25 image quality features extracted fromone image to differentiate the legitimate andimpostor samples.Its suitable for real time securitysystem in colleges,government sectors,privatesectors,etc.This method is very efficient comparedto previous state-of-the-art approaches.The cost ofthe method is very much reduced because thehardware is required to take the input only and theentire system is based on image processingsoftware.The time consumption is also reduced asthe recognition system is based on imageprocessing software and we take only one image asinput.And the security is very efficient as we take25 different features in one images likeMSE,NAE,AD,MD,etc.